1998
DOI: 10.1007/s11661-998-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

An analytical electron microscopy study of constituent particles in commercial 7075-T6 and 2024-T3 alloys

Abstract: To better understand the role of constituent particles in pitting corrosion, analytical electron microscopic studies were performed on the constituent particles in commercial 7075-T6 and 2024-T3 alloys. Five phases, namely, Al 23 CuFe 4 and amorphous SiO 2 in 7075-T6 and Al 2 CuMg, Al 2 Cu, and (Fe,Mn) x Si(Al,Cu) y in 2024-T3, were identified. The crystal structure and chemistry of the Al 23 CuFe 4 , Al 2 CuMg, and Al 2 Cu phases in these alloys are in good agreement with the published data. Small deviations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(91 citation statements)
references
References 9 publications
8
79
0
4
Order By: Relevance
“…2a). The EDX analysis revealed that particles contained Al, Fe, Cu, Zn, Mg, in accordance with previous works (Savas and Hearthman, 2008;Gao et al, 1998) that identified for example Al 23 CuFe phases (Gao et al, 1998) in similar aluminium alloys. The sample showed a metallic appearance, while the arithmetic roughness (R a ) was (0.9±0.1) µm.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2a). The EDX analysis revealed that particles contained Al, Fe, Cu, Zn, Mg, in accordance with previous works (Savas and Hearthman, 2008;Gao et al, 1998) that identified for example Al 23 CuFe phases (Gao et al, 1998) in similar aluminium alloys. The sample showed a metallic appearance, while the arithmetic roughness (R a ) was (0.9±0.1) µm.…”
Section: Resultssupporting
confidence: 91%
“…2b) with long spots including increasing contents of Zn, Mg and P. The high pH of the etching solution (pH = 11) favours both the chemical dissolution of the "type A" particles (Gao et al, 1998;Buchheit, 1995) and the immediate re-precipitation of their corresponding hydroxides and/or phosphates at the metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…The reason why compositional variation from batch to batch represents a difficulty is that the transition elements can be substitutional in many intermetallics. For example Ayer et al (Ayer, Koo et al 1985) found Zn and Ni in Al 7 Cu 2 Fe, and Gao et al (Gao, Feng et al 1998) found considerable compositional variation within a phase nominated as (Fe,Mn) x Si(Al,Cu) y with some particles containing mainly Fe and Cu with small amounts of Mn and others had significant Mn and Si; similar results were reported by Boag et al (Boag, Taylor et al 2010). Gao et al (Gao, Feng et al 1998) even found small amounts of Cr and Zn in Al 2 CuMg.…”
Section: Aa2xxxmentioning
confidence: 58%
“…So there is an assumption that a particular composition has a specific crystallographic structure which may not be valid. For example, Wei and coworkers (Gao, Feng et al 1998;Wei, Liao et al 1998) used TEM to study IM particles in AA2024-T3 and AA7075-T6 and found that compositions containing Al, Cu, Fe, Mn and Si, had a rhomohedral structure which did not match the hexagonal structure previously reported for particles of this type for example Al 8 Fe 2 Si or Al 10 Mn 3 Si. Classifying IM particles by shape is used both in metallurgy and corrosion.…”
Section: Aa2xxxmentioning
confidence: 92%
See 1 more Smart Citation